The Effect of Non Performing Loans, Third Party Funds, and Loan to Deposit Ratio on Credit Distribution - Rahmayanti, Indri Dwi; Lasmana, Andy; Melani, Maria Magdalena (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
One of the financial institutions that has been growing rapidly in supporting financing for small and medium enterprises is the Rural Bank. Based on Law Number 10 of 1998, a Rural Bank is a bank that conducts its business activities either conventionally or based on sharia principles. This study aims to analyze the effect of NPL, TPF, and LDR on credit distribution, both partially and simultaneously, in Rural Banks in Bogor Regency during the period 2018–2022. Additionally, this study seeks to measure the extent to which these three variables contribute to credit distribution. The method used in this study is a quantitative approach with a causal research design. The dependent variable in this study is credit distribution, while the independent variables include NPL, TPF, and LDR. The study population consists of 22 Rural Banks operating in Bogor Regency, with the sample selected using a purposive sampling technique. The sample comprises Rural Banks registered with the Financial Services Authority (Otoritas Jasa Keuangan/OJK) that meet the research criteria. Based on the analysis of the coefficient of determination (R-Square), a value of 0.887 was obtained. This indicates that TPF, NPL, and LDR collectively contributed 88.7% to credit distribution in Rural Banks in Bogor Regency during the 2018–2022 period.